Changes in the Mental Health Status of Rural Community-dwelling Elderly Over a Decade in Puducherry, South India: A Panel Study. - Ayyanar, Menaka; Sarkar, Sonali; Kattimani, Shivanand (Indian Journal of Community Medicine)
Context: Population aging is causing the rise in physical and mental illnesses, leading to the higher disability among the elderly. Despite advancements in healthcare, neglect of mental healthcare negatively impacts quality of life. Changes in the mental health status of the elderly people over time remains unexplored. Aims: To assess changes in the mental health status of elderly individuals in rural Puducherry, India, focusing on depressive symptoms, cognitive impairment, and factors associated with poor mental health. Settings and Design: Conducted in Thondamanatham, Puducherry, India, from March 2023 to March 2024, this panel study included individuals aged 60 and above. Elderly participants from a previous survey on mental health status in 2013 in the same village were traced and followed-up. Methods and Material: Three hundred twenty participants (72 from 2013 survey) were interviewed by using a Semi-structured questionnaire including the scales Geriatric depression scale-short form (GDS-15), Hindi Mini-Mental Status Examination (HMSE), Instrumental Activities of Daily Living (IADL), and the Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) in addition to the socio-demographic and self-reported morbidity details. Descriptive statistics and logistic regression were employed to analyses associations between mental health indicators and demographic variables. Results: Participants' average age was 69.8 years, with a majority falling within the 60–69 age group. Common health issues included vision impairment (53.1%), hypertension (41.9%), and diabetes mellitus (35.9%). The prevalence of cognitive impairment (54.4%) was notably higher than that of depressive symptoms (25.3%) and showed significant associations with employment status and hearing impairment. Depressive symptoms declined by 6.9%, while CI increased by 8.3% among 2013 participants. Conclusions: The study revealed decreasing depressive symptoms and increasing cognitive impairment among the elderly, along with positive behavioral changes regarding substance use.